Celebrity Endorsement Role, Brand Image, and Brand Credibility Influence Purchase Intention - Praditia Andryani; Lina Salim (Eduvest - Journal of Universal Studies, 2024)
This study aims to analyze the mediating effect of brand image on the role of celebrity endorsement and brand credibility on the purchase intention of the Samsung Z Flip 5 smartphone. This quantitative research uses structural equation modeling (SEM) with SmartPLS. The results of this study state brand credibility has a positive effect on brand image, and brand image mediates a direct effect on brand credibility with purchase intent. Meanwhile, brand credibility has no significant effect on purchase intent. Celebrity endorsements have no significant effect on brand image. Brand image does not mediate influence in the relationship between celebrity endorsements and purchase intent. The research's implications include the necessity of collaborating with stakeholders and fostering trust in order to raise interest in purchasing the Samsung Z Flip 5 smartphone.